1997
DOI: 10.1108/eum0000000005337
|View full text |Cite
|
Sign up to set email alerts
|

Designing and redesigning: Marquette Librarie’s Web site

Abstract: Examines the processes involved in creating a library/related Web site. Attempts to identify answers to the following questions: how a library should attempt to design or redesign a home page, why sites are needed, what content is required, how it is organized, what look is required, how is it evaluated and who is going to do the work? States future priority as being promotional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The following Frame 1 covers the studies on evaluation criteria of different Internet resources. Websites Clyde (2004), Stover and Zink (1996), King (1998), Novljan and Zumer (2004), Tillotson (2002), Chao (2002), Sapa (2005), Osorio (2001), McCready (1997), Xue (2004), Pacios (2003), Cohen and Still (1999), Schamber (1991), Zhang et al (2000).…”
Section: Criteria For Evaluating Of Different Internet Resourcesmentioning
confidence: 99%
“…The following Frame 1 covers the studies on evaluation criteria of different Internet resources. Websites Clyde (2004), Stover and Zink (1996), King (1998), Novljan and Zumer (2004), Tillotson (2002), Chao (2002), Sapa (2005), Osorio (2001), McCready (1997), Xue (2004), Pacios (2003), Cohen and Still (1999), Schamber (1991), Zhang et al (2000).…”
Section: Criteria For Evaluating Of Different Internet Resourcesmentioning
confidence: 99%
“…Literature on usability testing, which examines the steps that library users take in navigating the website, was prevalent (Battleson et al , 2001; Campbell, 2001). Except for the study of 133 websites (Tolppanen et al , 2000), studies undertaken on medium‐sized institutions have generally focused on usability at individual institutions only (Marquette University – McCready, 1997; Roger Williams University – McMullen, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investigating structured access to the library and Internet resources of the Schaffer library, Connolly and Golderman (1997) found that many potential users were unaware of access to library electronic resources. McCready's (1997) analysis also revealed that only 34 per cent of undergraduate students knew of the Marquette Libraries' home page. King's (1998) findings showed that 44 per cent of 120 Association of Research (ARL) libraries could be found in one step, while more than 47 per cent could be found after two or three steps.…”
Section: Introductionmentioning
confidence: 99%